Trauma & resuscitation - Mohamed, Rozilah @ Abdul Hadi (Institut Terjemahan & Buku Malaysia Berhad dan Universiti Islam Antarabangsa Malaysia, 2018)
Trauma is among the commonest presentation at the emergency room being the third highest mortality (28.6 percent) after coronary heart disease and septicaemia. The economic loss resulting from trauma has increased every year at the average rate of 9.7 percent since the past 3 decades. In order to equip the young doctors with vast knowledge and experience in this area, the Ministry of Health has introduced additional posting in the Anesthesiology and Critical Care as well as the Accident and Emergency departments during horsemanship training to ensure better management at the front line.